Heat transfer and pressure characteristics of Tri Ethylene Glycol/water and Ethylene Glycol/water mixtures in copper pipe heated flow systems - Sukarman, Sukarman; Khoirudin, Khoirudin; Amir, Amir; Fahrizin, Nazar; Azizah, Renata Lintang; Azizah, Azizah; Setiyo, Muji; Azmi, W. H. (SINERGI, 2025)
Enhancing heat transfer efficiency and pressure regulation in copper pipe flow systems is crucial for advancing modern cooling and heating technologies, particularly given the widespread use of copper piping in these applications. This study investigates the thermal and hydraulic performance of ethylene glycol/water (EG/water) and tri ethylene glycol/water (TEG/water) mixtures as working fluids in copper pipe systems. A series of controlled experiments was carried out on a dedicated copper pipe test section to evaluate the effects of varying flow rates on the heat transfer coefficient and pressure drop for each fluid mixture. The results indicate that the TEG/water mixture yielded a ~2.0% increase in heat transfer coefficient and a ~1.0% reduction in pressure drop compared to the EG/water mixture, with a corresponding increase in Reynolds number of approximately 37.0%. The reduction in pressure drop is primarily attributed to the lower viscosity of the TEG/water fluid. These findings provide valuable comparative insights into the thermophysical behaviour of both glycol-based mixtures and offer practical guidance for optimizing the selection of thermal fluids in large-scale cooling and heating systems that utilize copper piping.